Contribution of anthropogenic activities to the intensification of heat index-based spatiotemporally contiguous heatwave events in China - Kong, D; Xie, Y; Gu, X; Slater, LJE; Slater, L; Ci, H; Song, H (American Geophysical Union, 2024)
In this study, we identified heat index (HI)-based spatiotemporally contiguous heatwaves (HI-STHWs) in China based on meteorological observations and CMIP6 global climate model simulations. We analyzed the spatiotemporal patterns of changes in HI-STHWs in the past and future and quantitatively attributed these changes to anthropogenic activities. The results show that the duration, severity, average, maximum, and total impacted area of the annual strongest HI-STHWs during the present period of 1991–2014 are 1.77, 2.0, 1.05, 1.14, and 1.89 times the historical period of 1961–1990, respectively. In the fingerprint results, the anthropogenic greenhouse gases (GHG) signal is significantly detected, while the aerosol (AER) and natural (NAT) signals are not. GHG is the primary factor driving the intensification of HI-STHWs, which alone explains about 130%, 122%, 112%, 111%, and 114% of the above changes. The reason for GHG contribution exceeding 100% is that AER might have a negative contribution although nonsignificant. In the future warming climate, anthropogenic activities are projected to lead to more unprecedented HI-STHWs. Under the high emissions scenario of SSP585, by 2100, the annual strongest HI-STHW in China is projected to last almost the whole year and influence 96% regions of China in the most serious day. Meanwhile, its duration and total impacted area are 24.5 [17.2, 31.6] (90% confidence interval) and 107.2 [70, 129.9] times the preindustrial period. However, if the warming level could be limited to 2/1.5 °C, those values would be 3.4/5.4 and 8.2/16.2 times smaller than that under the SSP585 scenario by 2100.